A compendium of effective, evidence-based best practices in prevention of neurotrauma - Volpe, Richard (Book collections on Project MUSE., 2002)
Every year, thousands of people suffer unintentional neurotrauma injuries due to motor vehicle accidents, sports and playground injuries, and farm and occupational injuries. Although injury reduction targets have been established and indicators have been developed to measure progress in prevention, no method of evaluating and accessing effective injury prevention practices is currently available. This compendium aims to fill this gap by portraying exemplars that have the potential to reduce the incidence of these injuries, and by providing a detailed methodology that is effective in identifying innovative best practices. The intention of this work is not to be encyclopaedic; rather, the authors have reviewed the twenty-eight best and promising practices, taking into consideration the complexity of injury dynamics, and analysed what constitutes a best practice as the shift is made from individual clinical practice to the collective practice associated with policy implementation at the community level. The first worldwide assessment of best practices, this work is expected to be an important contribution to the emerging field of unintentional-injury prevention with its unique coverage of the life span, up-to-date bibliography, and directory of the major programs and professionals.